Volume 13: Nano-Manufacturing Technology; And Micro and Nano Systems, Parts a and B 2008
DOI: 10.1115/imece2008-67372
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Low-Cost, Rapid-Cycle Hot Embossing System for Microscale Parts

Abstract: Hot embossing is an effective technology for reproducing micro-scale features in polymeric materials, but large-scale adoption of this method is hindered by high capital costs and low cycle times relative to other technologies, and a general lack of manufacturing equipment. This work details a hot embossing machine design strategy motivated by maximum production speed and quality with minimal capital cost. The approach is to "right-size" the machine for specific product needs while making the design flexible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In figure 11 we compare experimentally measured [21] and simulated topographies near the centers of the three gratings for sample-average pressures of 0.5 MPa and 1.5 MPa, applied at 120 • C for 1.5 min. The simulations use the PMMA material model that was calibrated in our earlier work [12].…”
Section: Demonstration: Microfluidic Test Chipmentioning
confidence: 99%
“…In figure 11 we compare experimentally measured [21] and simulated topographies near the centers of the three gratings for sample-average pressures of 0.5 MPa and 1.5 MPa, applied at 120 • C for 1.5 min. The simulations use the PMMA material model that was calibrated in our earlier work [12].…”
Section: Demonstration: Microfluidic Test Chipmentioning
confidence: 99%
“…Previous work completed by Hale demonstrated that the design and construction of a simple, fast-cycle, low-cost embossing machine was feasible (14). However, this work also demonstrated a need for enhanced control over forming parameters and for mechanical precision and repeatability.…”
Section: Experimental Equipmentmentioning
confidence: 99%
“…Given sufficiently high temperatures and pressures, the micro-features will form to a high degree of fidelity, and any increased force or temperature will not significantly improve quality. However, excessively high temperatures and pressures will cause the polymer substrate to exhibit bulk flow, distorting the substrate and preventing subsequent registration for further finishing steps (14).…”
Section: Process Physics Of Hot Embossingmentioning
confidence: 99%
“…For this process a novel approach was taken to achieve both rapid cycle times and an overall low capital cost machine. The details of this approach can be found in [4]. The key features are a simple actuation system with limited travel, but precise force control.…”
Section: Hot Micro Embossing (Hme)mentioning
confidence: 99%
“…An earlier paper [17] highlights the factory's inception, with a team of more than 10 research assistants and 4 faculty members. The basis of our work is detailed in a number of papers including those on deformation properties of polymers [1][2], novel machine and process design for hot micro embossing and PDMS Casting [3][4][5] , tooling production and de-molding analysis [6][7][8], bonding methods [9] and methods for measurement and control of the resulting processes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%